Molecular & diagnostic imaging in prostate cancer: clinical applications and treatment strategies - Schatten, Heide (Advances in experimental medicine and biology, 2018)
Intro -- Preface -- Contents -- Contributors -- Chapter 1: Androgen Deprivation Therapy for Prostate Cancer -- 1.1 Historical Perspective -- 1.2 Sex Steroids in Prostate Cancer -- 1.2.1 Sources of Androgens -- 1.2.2 Androgens and the Androgen Receptor -- 1.3 Pharmacology of Hormonal Therapy for Prostate Cancer -- 1.3.1 Gonadal Androgen Ablation -- 1.3.2 Androgen Receptor Antagonists -- 1.3.3 Abiraterone -- 1.3.4 Enzalutamide -- 1.3.5 Five Alfa Reductases Inhibitors -- 1.3.6 ADT and FSH Escape -- 1.3.7 Testosterone Recovery After Castration -- 1.4 Hormonal Therapy in Non-metastatic Prostate Cancer -- 1.4.1 Hormonal Therapy Alone -- 1.4.2 Hormonal Therapy in Combination to Radiotherapy -- 1.4.3 Hormonal Therapy Adjuvant to Radical Prostatectomy -- 1.4.4 Hormonal Therapy at Biochemical Relapse After a Primary Treatment -- 1.5 Hormonal Therapy in Metastatic Prostate Cancer -- 1.5.1 Hormonal Therapy Alone -- 1.5.2 Hormonal Therapy Combination Regimens -- 1.6 Side Effects of Hormonal Therapy -- 1.6.1 Cardiovascular Disease -- 1.6.2 Metabolic Changes -- 1.6.3 Changes in Bone Health -- References -- Chapter 2: Advances in Radiotherapy for Prostate Cancer Treatment -- 2.1 Introduction to Radiotherapy for Prostate Cancer -- 2.2 Advances in External Beam Radiation Therapy (EBRT) for CaP -- 2.2.1 EBRT with Photon Beam -- 2.2.2 EBRT with Proton Beam -- 2.2.3 Robotic-Assistance in EBRT for Prostate Cancer Treatment -- 2.2.4 Challenges and Potential Future Directions in EBRT -- 2.3 Advances in Brachytherapy for CaP -- 2.3.1 Low-Dose-Rate (LDR) Brachytherapy -- 2.3.2 High-Dose-Rate (HDR) Brachytherapy -- 2.3.3 Challenges and Potential Future Directions in Brachytherapy -- 2.4 Discussion/Conclusion -- References -- Chapter 3: Role of Prostate MRI in the Setting of Active Surveillance for Prostate Cancer -- 3.1 Introduction.
Description based on publisher supplied metadata and other sources